Identification and Functional Characterization of Two Putative Pheromone Receptors in the Potato Tuber Moth, Phthorimaea operculella - He, Xiaoli; Cai, Yajie; Zhu, Jinglei; Zhang, Mengdi; Zhang, Yadong; Ge, Yang; Zhu, Zengrong; Zhou, Wenwu; Wang, Guirong; Gao, Yulin (Frontiers in Physiology, 2021)
Pheromones are organismal odors that evoke innate responses in conspecifics. In moth, pheromone components can be detected by specialized olfactory receptor neurons (OSNs) housed in long sensilla trichoid on the male antennae. The pheromone receptors (PRs) located in the dendrite membrane of OSNs are responsible for pheromone sensing in most Lepidopteran insects. The potato tuber moth Phthorimaea operculella is a destructive pest of Solanaceae crops. Although sex attractant is widely used in fields to monitor the population of P. operculella, it remains unclear how the male moth of P. operculella recognize sex pheromone components. In the present study, we cloned two pheromone receptors genes PopeOR1 and PoprOR3 in P. operculella. The transcripts of them were highly accumulated in the antennae of male adults. Functional analysis using the heterologous expression system of Xenopus oocyte demonstrated that these two PR proteins both responded to (E4, Z7)-13: Ac and (E4, Z7, Z10)-13: Ac, the key sex pheromone components of P. operculella, whilst they responded differentially to these two ligands. Our findings for the first time characterized the function of pheromone receptors in gelechiid moth and could promote the olfactory based pest management of P. operculella in the field.